Protecting H.264/AVC Data-Partitioned Video Streams over Broadband WiMAX. (23rd August 2012) - Al-Jobouri, Laith; Fleury, Martin; Ghanbari, Mohammed
Abstract : Broadband wireless technology, though aimed at video services, also poses a potential threat to video services, as wireless channels are prone to error bursts. In this paper, an adaptive, application-layer Forward Error Correction (FEC) scheme protects H.264/AVC data-partitioned video. Data partitioning is the division of a compressed video stream into partitions of differing decoding importance. The paper determines whether equal error protection (EEP) through FEC of all partition types or unequal error protection (UEP) of the more important partition type is preferable. The paper finds that, though UEP offers a small reduction in bitrate, if EEP is employed, there are significant gains (several dBs) in video quality. Overhead from using EEP rather than UEP was found to be around 1% of the overall bitrate. Given that data partitioning already reduces errors through packet size reduction and differentiation of coding data, EEP with data partitioning is a practical means of protecting user-based video streaming. The gain from employing EEP is shown to be higher quality video to the user, which will result in a greater take-up of video services. The results have implications for other forms of prioritized video streaming.